2022
DOI: 10.1002/edn3.309
|View full text |Cite
|
Sign up to set email alerts
|

High diversity of lysis‐resistant cells upon the application of targeted physical and chemical lysis to environmental samples originating from three different water bodies

Abstract: In most habitats, fluctuating environmental conditions create periods of compromised survival for metabolically active organisms. In response, various survival strategies have evolved, including the formation of resilient resting cells. We assessed the biodiversity of the lysis‐resistant bacteria in three different environments by applying a harsh physicochemical treatment to the samples. The bacterial diversity of the lysis‐resistant fraction was compared with the bacterial diversity from the same environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 125 publications
0
3
0
Order By: Relevance
“…Figure 6E and F showed that most ASVs in both environments (lake sediments and microbial mats) were either enriched in the total community or in the lysis-resistant fraction, with only a small proportion of them showing similar abundance in both fractions (index values 0.2-0.8). However, in contrast to Bacteria where OTUs would tend to be consistently found in either fraction [28], for Fungi, this is not the case and ASVs were found equally in both fractions in different environmental samples (Additional Fig. 3).…”
Section: Beyond Known Taxamentioning
confidence: 89%
See 1 more Smart Citation
“…Figure 6E and F showed that most ASVs in both environments (lake sediments and microbial mats) were either enriched in the total community or in the lysis-resistant fraction, with only a small proportion of them showing similar abundance in both fractions (index values 0.2-0.8). However, in contrast to Bacteria where OTUs would tend to be consistently found in either fraction [28], for Fungi, this is not the case and ASVs were found equally in both fractions in different environmental samples (Additional Fig. 3).…”
Section: Beyond Known Taxamentioning
confidence: 89%
“…This was the basis to develop a method that uses physical and chemical treatments to lyse non-resistant cells and to enrich lysis-resistant structures [27]. When applied to bacterial communities, the procedure results in the enrichment of endospores from Firmicutes, but also lysis-resistant spores from other bacteria such as Actinobacteria or Cyanobacteria [28]. Even though in the case of the various structures promoting survival in fungi, their enhanced resistance to lysis has not been assessed systematically, previous studies have shown that lysis of survival structures such as spores requires harsher conditions [29], and that modifications in the spore wall composition and structure promote resistance [30].…”
Section: Introductionmentioning
confidence: 99%
“…Firmicutes are spore formers; and further, spore formation is a survival trait to survive challenging environments such as the cold. Firmicutes have been reported to be lysis resistant during the DNA extraction process (Junier et al 2022). Therefore, it is possible during the DNA extraction procedure that we were unsuccessful in lysing Firmicutes, leading to their absence in the microbial-community data.…”
Section: Microorganisms Isolated From Snow Containing Particulate Mattermentioning
confidence: 99%
“…This method uses physical and chemical treatments to lyse non-resistant cells and to enrich lysis-resistant structures. The procedure results in the enrichment of endospores from Firmicutes, but also lysis-resistant cell forms from other bacteria (25). Moreover, the use of the lysis-enrichment method has been recently extended to study lysis-resistant communities in archaea.…”
Section: Introductionmentioning
confidence: 99%